2011
DOI: 10.1159/000324863
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Adult Cardiovascular Disease following Exposure to Late-Gestation Hyperglycemia

Abstract: Background: In utero exposure to hyperglycemia is becoming increasingly prevalent as the number of women entering pregnancy with type II diabetes, or developing gestational diabetes, increases. Both animal studies and epidemiologic investigations have found cardiovascular abnormalities in adult offspring of hyperglycemic mothers (OHM). Objective: We hypothesized that adult OHM would have abnormal cardiac function in vivo and increased susceptibility to ischemia. Methods: Pregnant rats were made diabetic on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…Representative photomicrographs of renal cortex [immunoreaction for tyrosine hydroxylase (TH); positive reaction in dark brown: OC-Sham ϭ offspring from control mother -sham; OC-dn ϭ offspring from control mother -denervated; OD-Sham ϭ offspring from diabetic mother, sham; OD-dn ϭ offspring from diabetic mother, denervated]; and comparison of tyrosine hydroxylase protein expression in renal tissues by Western blot (WB) analysis (*P Յ 0.05 compared offspring from control mothers sham, †P Յ 0.05 compared offspring from diabetic mothers sham). (2,11,12,40,51,52,67). Hypertension develops early in life, before 2 mo in rats, and blood pressure increases by up to 30 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative photomicrographs of renal cortex [immunoreaction for tyrosine hydroxylase (TH); positive reaction in dark brown: OC-Sham ϭ offspring from control mother -sham; OC-dn ϭ offspring from control mother -denervated; OD-Sham ϭ offspring from diabetic mother, sham; OD-dn ϭ offspring from diabetic mother, denervated]; and comparison of tyrosine hydroxylase protein expression in renal tissues by Western blot (WB) analysis (*P Յ 0.05 compared offspring from control mothers sham, †P Յ 0.05 compared offspring from diabetic mothers sham). (2,11,12,40,51,52,67). Hypertension develops early in life, before 2 mo in rats, and blood pressure increases by up to 30 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of diabetic mothers have an increased risk of cardiovascular disease and diabetes in adulthood (2,13,42). A recent meta-analysis concluded that offspring of diabetic mothers have higher systolic blood pressure than controls (1).…”
mentioning
confidence: 99%
“…Indeed, increasing evidence shows that exposure to hyperglycemia in utero induces not only short-term consequences, but also long-term effects such as congenital birth defects and metabolic syndrome (Metzger et al 2008;Simeoni et al 2009). These defects are most common and severe in the central nervous and cardiovascular systems (Agoudemos et al 2011;Zhao et al 2010). The molecular basis of CHD pathogenesis in pregestational diabetes remains largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Both alterations in the expression of PPARα and overaccumulation of lipids have been found in the heart in the experimental models of adverse intrauterine programming due to protein restriction . Besides, studies have shown that diabetes experimentally induced in rats during late gestation leads to the programming of cardiovascular alterations in the offspring . Damage in the offspring's heart has also been found in severe models of pregestational diabetes .…”
Section: Introductionmentioning
confidence: 99%